Gamified Flipped Classroom and Effective Learning Outcomes Through Bibliometric and Systematic Literature Review Toward SDGs 4 - Elizabeth Lobo; Yerry Soepriyanto; Ence Surahman (Jurnal Penelitian Pendidikan IPA, 2025)
The use of appropriate approaches or methods in learning can increase the effectiveness of learning outcomes in accordance with the goals of quality education in SDGs 4. The development of flipped classroom or flipped learning and gamification is increasing year by year. So it is necessary to know the application of flipped classroom with the help of gamification in learning for effective learning outcomes toward SDGs 4. The research on gamified flipped classroom uses systematic methods of literature review and bibliometrics to determine the development of trends GFC over a period of 10 years from 2015- October 26, 2025. Data was taken from the Scopus database with the inclusion criteria of English-language journal articles and was all open access. The results of bibliometric analysis show that research on gamification and flipped classroom or flipped learning began in 2016, while research on flipped classroom with the help of gamification began in 2018. Several countries conduct GFC research quantitatively, such as Spain, Thailand, Hong Kong, Indonesia. GFC is mostly carried out at the university level and is widely applied to the subject areas of social science (30.20%) and computer science (22.60%).